Strategic Zakat Management for The Socio-Economic Empowerment of Converts: A Study of Amil Zakat Institution - Muchlis, Zaini; Saleh, Muhammad Aunurrochim Mas’ad (Universitas Ahmad Dahlan, 2025)
This study aims to determine the concept of empowering converts through zakat philanthropy funds carried out by amil zakat institutions in improving the welfare of converts, and to analyze the impact of empowering zakat on converts in Indonesia. In general, this research can provide benefits to the community regarding the management and empowerment of zakat for converts, and become material for information and consideration, both conceptually, theoretically and programs for managing zakat funds at amil zakat institutions. The methodology used in this research is through a qualitative descriptive analysis with a comparative approach, while the object of this research is the National Amil Zakat Agency and the Arimatea Amil Zakat Institute related to the management of zakat and the empowerment of converts in Indonesia. Data collection techniques in this study were carried out by interviewing informants, direct observation and documentation. The data obtained in this study were processed qualitatively and analyzed systematically in relation to the observation of written data. The results of this study indicate that there is a collaboration in empowering zakat for converts carried out by the two amil zakat institutions, where both have various strategies in their management, such as exchanging data on converts in Indonesia, collaboration related to converts' economic activities in the form of direct assistance or development of household economics, and provision of capital to small businesses. The impact of implementing zakat for converts is to gain specific and sustainable reinforcement in the fields of religion, education, and economic improvement.